Assessment of Women's Knowledge about Postpartum Depression: Penilaian Pengetahuan Wanita tentang Depresi Pascapersalinan - Ebtihal Sattar Qassim (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Postpartum depression is a major public health concern affecting maternal mental health and child well-being worldwide. Specific Background: Limited knowledge and awareness among postnatal mothers contribute to delayed recognition, stigma, and low help-seeking behavior, particularly in developing settings. Knowledge Gap: Despite increasing global attention, evidence regarding the level of postpartum depression literacy and associated factors among postnatal mothers in the study setting remains insufficient. Aims: This study aimed to assess the level of knowledge and awareness of postpartum depression among postnatal mothers and to identify related sociodemographic characteristics. Results: The findings indicate that a considerable proportion of mothers demonstrated inadequate understanding of symptoms, risk factors, screening, and available treatment options. Educational level, prior information exposure, and contact with health services were associated with higher literacy levels. Misconceptions and stigma-related beliefs were still present among respondents. Novelty: This study provides updated empirical data on postpartum depression literacy within the local maternal population, highlighting specific domains of misunderstanding that require targeted educational strategies. Implications: Strengthening maternal mental health education through antenatal and postnatal services, including routine screening and counseling by healthcare professionals, is essential to promote early detection and appropriate support for affected mothers. Keywords: Postpartum Depression, Maternal Mental Health, Depression Literacy, Postnatal Mothers, Mental Health Awareness Key Findings Highlights: A substantial proportion of respondents showed limited understanding of symptoms and risk factors. Sociodemographic characteristics were associated with variations in literacy levels. Misconceptions and stigma-related beliefs remained evident among participants.